Mass Cytometry for the Assessment of Immune Reconstitution After Hematopoietic Stem Cell Transplantation - Stern, Lauren; McGuire, Helen; Avdic, Selmir; Rizzetto, Simone; Fazekas de St Groth, Barbara; Luciani, Fabio; Slobedman, Barry; Blyth, Emily (Frontiers in Immunology, 2018)
Mass cytometry, or Cytometry by Time-Of-Flight (CyTOF), is a powerful new platform for high-dimensional single-cell analysis of the immune system. It enables the simultaneous measurement of over 40 markers on individual cells through the use of monoclonal antibodies conjugated to rare-earth heavy metal isotopes. In contrast to the fluorochromes used in conventional flow cytometry, metal isotopes display minimal signal overlap when resolved by single-cell mass spectrometry. This review focuses on the potential of mass cytometry as a novel technology for studying immune reconstitution in allogeneic haemopoietic stem cell transplant (HSCT) recipients. Reconstitution of a healthy donor-derived immune system after HSCT involves the coordinated regeneration of innate and adaptive immune cell subsets in the recipient. Mass cytometry presents an opportunity to investigate immune reconstitution post-HSCT from a systems-level perspective, by allowing the phenotypic and functional features of multiple cell populations to be assessed simultaneously. This review explores the current knowledge of immune reconstitution in HSCT recipients and highlights recent mass cytometry studies contributing to the field.